Successful treatment of Gorham–Stout syndrome in the spine by vertebroplasty with cement augmentation: A case report and literature review. Issue 29 (July 2018) - Liu, Shuzhong; Zhou, Xi; Song, An; Kong, Xiangyi; Wang, Yipeng; Liu, Yong
Abstract: Rationale: Gorham-Stout syndrome in the spine is extremely rare, and there is no standard curative management thus far. The objective of this article is to report a very rare case of Gorham-Stout syndrome of the lumbar and sacral spine with chylothorax and chyloperitoneum successfully treated by combination of vertebroplasty with cement augmentation and medication treatment. We described the clinical characteristics and postoperative therapy of the patient, and reviewed all of the published cases of Gorham-Stout syndrome of the lumbar and sacral spine. Patient concerns: A 31-year-old man presented with increasingly serious abdominal distention and back pain. MRI showed massive bony destruction of the spine and pelvis. CT and ultrasonography demonstrated massive ascites and mild hydrothorax. Diagnoses: We believe this is the first report of a case of Gorham-Stout syndrome with both chylothorax and chyloperitoneum. Interventions: Chest and abdominal cavity puncture was performed for symptomatic relief and the test results confirmed chylothorax and chyloperitoneum. Tissue biopsy and percutaneous vertebroplasty at L5 were performed and the postoperative pathology together with symptoms and examinations were reported to be consistent with Gorham-Stout syndrome. Subsequently, we administered combination medical treatment consisting of interferon-α-2b, zoledronic acid and calcitriol. Outcomes: At the 1-year and 2-year follow-up visit, he had nearly full complete remission and reported palliative back pain. Moreover, the amount of pleural and peritoneal fluid was successfully reduced gradually. Lessons: Vertebroplasty by cement augmentation may be a treatment option for patients with Gorham-Stout Syndrome in the spine who cannot undergo appropriate surgery or decline open surgery. This represents a safe and minimally invasive approach to sustainably relieve pain and stabilize vertebral bodies with Gorham-Stout syndrome in the spine.